2013
DOI: 10.1111/str.12052
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐State Creep Analysis of Functionally Graded Rotating Cylinder

Abstract: Axi-symmetric component like cylinder etc. has to operate under severe thermo-mechanical loads, which cause significant creep. It, thus, reduces its service life. The present study investigates the steady-state creep in a functionally graded rotating cylinder at constant angular speed. The cylinder is made up of aluminium matrix and reinforced with silicon carbide particles. The thermal gradient in the functionally graded rotating cylinder is estimated by performing finite element analysis on ANSYS software (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mangal et al 36 who studied the steady-state creep analysis of FG rotating cylinders concluded that σ r , σ θ , σ a , and σ e in the cylinder are significantly affected by the presence of a particle gradient as well as by the presence of a particle and a thermal gradient. It was found that the creep rate was significantly reduced by the simultaneous presence of particle and thermal gradients which increased the lifetime of the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Mangal et al 36 who studied the steady-state creep analysis of FG rotating cylinders concluded that σ r , σ θ , σ a , and σ e in the cylinder are significantly affected by the presence of a particle gradient as well as by the presence of a particle and a thermal gradient. It was found that the creep rate was significantly reduced by the simultaneous presence of particle and thermal gradients which increased the lifetime of the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…19 The use of FGMs in applications involving stringent thermo-mechanical loadings helps in reducing the stresses and deformations, which enhances the useful service life of engineering components. 24,614 It is possible due to flexibility of tailoring the distribution of reinforcement in a certain spatial direction in the FGM structures, so as to attain the desired variation of the required properties. 15…”
Section: Introductionmentioning
confidence: 99%